Evaluating Emulsion Dynamics: The Role of Surfactants and Mixing Conditions in Non-Baffled Configurations - Kanani, Nufus; Kustiningsih, Indar; Wardhono, Endarto Yudo; Wardalia, Wardalia; Heriyanto, Heri; Adiwibowo, Muhammad Triyogo; Rusdi, Rusdi; Hartono, Rudi; Demustila, Harly; Damayanti, Demietrya Renata Sashi; Maulida, Alyssa Shafira; Priyatna, Aufa Irsyad (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2024)
The study investigates the impact of surfactant concentration and mixing time on the physical properties and stability of emulsions in non-baffle mixing systems. Surfactants, known for their ability to reduce interfacial tension, play a pivotal role in enhancing emulsion stability by promoting uniform droplet dispersion and reducing coalescence. Experiments were conducted using varying surfactant concentrations (0, 5, and 10 mL) to evaluate their effects on key parameters such as density, viscosity, Reynolds number, emulsion height, and stability over time. The results revealed that higher surfactant concentrations significantly improved emulsion uniformity and stability, with the 10 mL concentration yielding the most consistent outcomes. However, the absence of baffles introduced challenges, including prolonged mixing times and stratification tendencies, underscoring the need for optimized mixing configurations. These findings have practical implications for industries reliant on stable emulsions, highlighting the importance of balancing surfactant concentration and mixing dynamics to achieve efficient and cost-effective processes.